Pengaruh Social Support terhadap Career Adaptability pada Mahasiswa Akhir di Kota Bandung: Pengaruh Social Support Terhadap Career Adaptability Pada Mahasiswa Akhir di Kota Bandung - Anabila Zahra Auliya; Siti Qodariah (Bandung Conference Series: Psychology Science, 2024)
Abstract. Final students are required to have preparation in future career planning to avoid difficulties in job search later. The difficulty in finding a job has a relationship with the gap between the competencies needed and the competencies possessed by students due to the lack of readiness of new graduates in career adaptation. It is known that there are only twenty percent of college graduates who work in accordance with their study program while the rest work outside the study program. This indicates that final year students need to be equipped with an understanding of career adaptability for self-adjustment in the work environment. Many factors can influence, one of which is social support. This study aims to determine how much influence social support has on career adaptability in final year students in Bandung. There were 206 final year students as respondents who participated in this study. The measuring instruments used are Career Adapt-Abilities Scale (CAAS) for Career Adaptability and The MOS-Social Support Survey (MOS-SSS) for Social Support. The research design used is quantitative with causality method and the sampling technique used is convenience sampling and the analysis technique used is simple regression. The results of statistical tests obtained the influence of social support on career adaptability in final year students in the city of Bandung with a contribution of 10.2% with a significance value of 0.00 <0.05. Abstrak. Mahasiswa akhir dituntut memiliki persiapan dalam perencanaan karir masa depan untuk menghindari kesulitan dalam pencarian kerja nantinya. Kesulitan mendapat pekerjaan memiliki hubungan dengan kesenjangan antara kompetensi yang dibutuhkan dengan kompetensi yang dimiliki mahasiswa akibat dari kurangnya kesiapan dalam adaptasi karir. Diketahui hanya terdapat dua puluh persen lulusan perguruan tinggi yang bekerja sesuai dengan program studinya sementara sisanya bekerja di luar prodi. Hal ini mengindikasikan jika mahasiswa tingkat akhir memerlukan pembekalan pemahaman career adaptability untuk penyesuaian diri di lingkungan kerja. Banyak faktor yang dapat mempengaruhi, salah satunya yakni dukungan sosial. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh social support terhadap career adaptability pada mahasiswa tingkat akhir di kota Bandung. Terdapat 206 mahasiswa tingkat akhir sebagai responden yang berpartisipasi dalam penelitian ini. Alat ukur yang digunakan yakni Career Adapt-Abilities Scale (CAAS) untuk Career Adaptability dan The MOS-Social Support Survey (MOS-SSS) untuk Social Support. Desain penelitian yang digunakan yakni kuantitatif dengan metode kausalitas dan teknik sampling yang digunakan yakni convenience sampling dan teknik analisa yang digunakan yakni regresi linear sederhana. Hasil uji statistik diperoleh pengaruh social support terhadap career adaptability pada mahasiswa tingkat akhir di kota Bandung dengan kontribusi sebesar 10.2% dengan nilai signifikansi 0.00 < 0.05.